Pengaruh Gender dan Dukungan Politik terhadap Kinerja Pemerintah Daerah - Fadillah Ahmad Fauzi Pratama; Doddy Setiawan (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This study aims to investigate how gender and political support influence the performance of local governments in Java. This study is based on public policy theory. This study also examines several control variables related to regional characteristics such as local government size, capital expenditure, and regional wealth levels. The sample in this study consisted of all regencies/cities in Java, namely 113 regencies/cities, and the observation period was from 2016 to 2018. The results of this study indicate that local government performance is influenced by gender and political support. This study also conducted further tests such as analysis of non-expansion areas, which yielded consistent results.